Comparative Renoprotective Effect of Febuxostat and Allopurinol in Predialysis Stage 5 Chronic Kidney Disease Patients: A Nationwide Database Analysis. Issue 5 (17th December 2019) - Hsu, Yun‐Shiuan O.; Wu, I‐Wen; Chang, Shang‐Hung; Lee, Cheng‐Chia; Tsai, Chung‐Ying; Lin, Chan‐Yu; Lin, Wan‐Ting; Huang, Yu‐Tung; Wu, Chao‐Yi; Kuo, George; Hsiao, Chih‐Yen; Lin, Hsing‐Lin; et al.
Abstract : Hyperuricemia has been associated with chronic kidney disease (CKD) progression. The antihyperuricemic febuxostat's potential renoprotective effect has been demonstrated in stage 1–3 CKD. Large‐scale studies comparing the renoprotective potential of febuxostat and allopurinol in advanced CKD are lacking. We exclusively selected 6, 057 eligible patients with predialysis stage 5 CKD prescribed either febuxostat or allopurinol using the National Health Insurance Research Database in Taiwan during 2012–2015. There were 69.57% of allopurinol users and 42.01% febuxostat users who required long‐term dialysis ( P  < 0.0001). The adjusted hazard ratio (HR) of 0.65 (95% confidence interval (CI) 0.60–0.70) indicated near 35% lower hazards of long‐term dialysis with febuxostat use. The renal benefit of febuxostat was consistent across most patient subgroups and/or using the propensity score‐matched cohort. The adjusted HR was 0.66 (95% CI, 0.61–0.70) for long‐term dialysis or death. In conclusion, lower risk of progression to dialysis was observed in predialysis stage 5 CKD febuxostat users without compromising survival.